Ecomorfologia e padrões de abundância de Labridae em ilha oceânicas e áreas da costa brasileira - Ferreira, Gabriel Costa Cardozo (2015)
Relationships between morphological adaptationsand species ecology are the subject of ecomorphology studies that covers the form-function complex as an indicator of performanceand survival of organisms in a habitat. This performance is a reflection offunction that each species develop at the environment. Ecomorphologicaland functional analysis allow evaluate diversityand redundancy of species in functional groups, with crucial implications to understanding the resilienceand implementing actions to conservation of reef environments. Labridae family is known for morphological variation in 616 species, including ontogenetic shifts that lead to a great diversity of ecological roles, as variations in a micro-habitats occupancyand its impact over benthiccommunities. The present work aimed (i) propose a functional group classification to South-Western labrids, (ii) examine how the ontogenetic changes affect the functional role of the species, (iii) evidence which morphological characteristics drive this variations,and (iv) infer about the the ecological roleand the environmental relative importance of each specie, according to ecologicaland ecomorphological data. Morphometric analysis were performed in 21 species, divide in three developing classes (juveniles, intermediariesand adults). From functional attributes derived of this measurements were performed principal component analysisand clusters of consensual trees to each classand to the set of all classes, aiming to explain the morphological variationsand the different functional roles linked to species ontogeny. Analyses produce nine functional groups described according with the trophic guild, living habitsand ontogenetic stages. The attributes that drives the group formationand its functionaland morphological variations were: “Oral surface”, “Oral width”, “Body elongation index”and “Dentition type”. Species as Cryptotomus roseus, Clepticus brasiliensis, Halichoeres penrosei, Scarus zelindaeand Xyrichtys novaculapresent different functional groups during ontogeny, playing varied ecological roles in the ecosystems that inhabits.